Avaliação do tempo de inundação/drenagem de um sistema wetland tipo tidal-flow no tratamento de esgoto sanitário sintético - Pacheco, Amanda (2022)
This study evaluated a Tidal-Flow Constructed Wetland performance when treating low concentration synthetic wastewater (COD < 250 mg L-1) under a subsurface flow. The constructed wetland, with a working volume of 117 L, was filled with fragments of bricks (51 cm, 44% porosity) and expanded clay (4 cm). The constructed wetland was vegetated with Alternanthera philoxeroides (Mart.) Griseb., (32 plants m-²). The experiment was divided into 4 stages, each one with a 24-hour cycle: Stages I (12h full/12h empty) and II (20h full/ 4 h empty) had only one tide, while stages III (6 h full/6 h empty) and IV (10 h full/ 2h empty) had two tides. The removal efficiencies of chemical oxygen demand were 65% to 80% with the filtered sample and 75% to 90% with the gross sample, and no significant differences were observed among these samples. The removal efficiencies of Kjeldahl total nitrogen achieved 61% to 69% and also no significant differences were observed. All stages have significantly removed ammoniacal nitrogen, achieving 73.47% in Stage I, 56,50% in Stage II, 79.43% in Stage III, and 75.61% in Stage IV, but the samples of Stage II showed a lower removal efficiency compared to Stages III and IV. Nitrite concentration remained the same in the influent and the effluent only in Phase III, while nitrate concentration values remained the same in Stages I, II, and III, with a significant reduction in the concentration in Stage IV. Although the removal of nitrite and nitrate was not observed in all stages, the removal of total nitrogen was observed in all stages. The total phosphorus removal efficiency in Stage I (28%) and Stage III (38%) was significantly lower than in Stages III (65%) and IV (64%) indicating that the presence of a tide possibly had improved the removal of this parameter. Regarding the microbial community, the Stage IV sample showed the highest α diversity. The assessment of β diversity confirmed that the operational condition influenced the structure of the microbial community. The highest relative abundance of microorganisms detected in all samples has nitrifying and denitrifying potential. Possibly the nitrogen removal occurred via heterotrophic nitrification followed by aerobic denitrification. The removal of phosphorus by the bricks was 0.03 mg g-1 and the removal of nitrogen by the bricks was negligible. Plants removed 0.80% and 1.03% of phosphorus and nitrogen, respectively. Considering the overall performance of the Tidal-Flow Constructed Wetland in pollutants removal, Stage IV presented the best performance, concluding that the different operating conditions influenced the phosphorus and nitrogen removal efficiency, not affecting the organic matter removal efficiency in terms of COD.